Serum value of Fasting C-peptide (FC-P), fasting insulin (FIns), and glycated hemoglobin (HbA1c) after Dynamic Blood Glucose Monitoring-guided Personalized Nutrition and Insulin Pump Therapy for Type II Diabetes Mellitus : Serum value of Fasting C-peptide (FC-P), fasting insulin (FIns), and glycated hemoglobin (HbA1c) - Zhu, Guohong (Journal of Medical Biochemistry, 2025)
Introduction: type 2 diabetes mellitus (T2DM) is a chronic metabolic disease requiring comprehensive management of multiple risk factors including blood glucose (BG), blood pressure, and lipids. It to investigate the clinical effects of individualized nutrition and insulin pump therapy guided by continuous glucose monitoring (CGM) based on the quality circle control (QCC) nursing model in T2DM patients and its effect on Fasting C-peptide (FC-P), fasting plasma glucose (FPG), 2-hour postprandial glucose (2 hPG), fasting insulin (FIns), and glycated hemoglobin (HbA1c). Materials and Methods: eighty T2DM patients treated at our hospital from January 2023 to January 2024 were recruited and rolled into a research group (EG) receiving individualized nutrition and insulin pump therapy guided by CGM based on the QCC nursing model, and a regular group (RG) receiving routine care and treatment. Differences of BG control, insulin usage, CGM downtime, and anomaly occurrence rate were compared between groups. Results: EG showed marked improvements relative to RG in mean fasting C-peptide (FC-P), fasting plasma glucose (FPG), postprandial 2-hour glucose (2 hPG), fasting insulin (FIns), and glycated hemoglobin (HbA1c) levels (P<0.05). It also reduced time to achieve BG targets, lowered glucose variability and insulin dosage, and decreased the incidence of CGM system anomalies (P<0.05). Treatment effectiveness and nursing satisfaction were markedly higher in EG versus RG (P<0.05). Conclusion: the QCC nursing model effectively enhances BG control, optimizes insulin therapy, improves dietary habits and quality of life, and reduces hypoglycemic events in T2DM patients. This model deserves promotion and application in clinical practice.